Evaluating the Performance of Private and Public Mutual Funds - Atul Babasaheb Gaware, Sonali Sunil Jadhav, Shoyab Tayer Shaikh, Vaishali Nilesh Chaudhari, Samadhan Bundhe, Mohit Babasaheb Gaware (European Economic Letters (EEL), 2024)
Introduction: Mutual funds are a very important financial market scheme in the current economy as it deals with multiple investments and market shares. It can boost the economy of developing nations by a significant amount. Aim: The study aims to know the value of Mutual funds in the improvement level of sectors in private and public. Literature Review: Mutual funds have many advantages like liquidity, diversification of markets, management by experts in finances, bulk transactions in billions of dollars and most importantly work through a cost-efficient process. Methodology: Primary quantitative method is used to collect data and relevant information from the survey questionnaire. 55 participants took part in the survey and their responses were recorded. Findings: It was found that mutual funds have huge benefits in terms of an economic boost for developing nations and it provides ample opportunities to invest for a hefty return. Discussion: Transaction challenges and risks are the most important in terms of issues seen in mutual funds markets. Despite all the risks, the mutual funds market is an emerging asset of economies in developing economic nations. Conclusion: Mutual funds in private and public sectors have huge potential in terms of market boost and economic advancements.